Environmental Linguistic Narratives in the Poetry of Elementary School Teacher Education Students - Nurhaedah Nurhaedah; Juanda Juanda (Universitas Cokroaminoto Palopo, 2026)
Ecological metaphors in the poetry of Elementary School Teacher Education students provide important insights into how prospective teachers conceptualize environmental realities and human–nature relationships. Examining these metaphors is essential for understanding the ecological awareness and ideological orientations embedded in their poetic language. This requires a deeper understanding of how prospective educators frame ecological realities through the use of figurative language. This study aims to reveal the structure of ecological metaphors and environmental framing orientation in the poetry of elementary school teacher education students through the integration of cognitive linguistics and ecolinguistics, placing metaphors as cognitive mechanisms as well as indicators of language ideology. The research data consisted of 50 poems by third-semester PGSD students that explicitly represented environmental or nature issues, collected through academic assignment documentation, selected based on thematic criteria, and analyzed using an interactive analysis model that included data condensation, data presentation, and conclusion drawing or verification. The results of the analysis show the dominance of structural metaphors over orientational and ontological metaphors, which indicates a tendency to construct nature as a role-playing and acting entity, as well as to assess ecological degradation through a relational moral and affective framework. Oriental patterns organize environmental evaluation through spatial and directional value schemes, while ontological metaphors condense abstract concepts into objects of action such as hope, change, and inheritance. The research contributes to enriching cognitive linguistics and ecolinguistics studies, providing an empirical basis for developing environmental literature curricula for prospective teachers, supporting transformative environmental education policies, and strengthening SDG achievements, particularly quality education and climate action.